HUBUNGAN PERSEPSI KERENTANAN DAN SELFEFFICACY DENGAN PERILAKU PENGENDALIANHIPERTENSI PADA LANSIA PENYANDANG HIPERTENSI SAAT PANDEMI COVID - 19 WILAYAH KERJA PUSKESMAS KELURAHAN GROGOL SELATAN RW 01 - Nada Naflah, (2021)
Elderly is an age that is prone to suffer from hypertension because in the elderly there is a decrease in organ function. Hypertension can cause various complications, especially during the COVID-19 pandemic. It is important for the elderly to be able to control the severity of their hypertension. The perception of susceptibility is one of the factors that influence the control of hypertension because it can try to reduce the risk of developing health problems. Self efficacy also affects in controlling hypertension because it can increase self efficacy and motivation. This type of research is a quantitative research with a cross sectional approach. The population in this study were elderly people with hypertension in RW 01, Grogol Selatan Village. The sampling technique used is total sampling with a total sample of 71 respondents. The analysis used in this research is univariate analysis and bivariate analysis using chi square test. There is a relationship between perceived of susceptibility and hypertension control behavior with p value: 0.004 There is a relationship between self-efficacy and hypertension control behavior with p value: 0.000